(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The process of translation has always supported human communication by crossing the gap between languages and cultures. Artificial Intelligence (AI) is a new paradigm that revolutionized multiple sectors and this has specifically affected text machine translation, decreasing or eliminating human involvement. As a result, translation software models based on artificial intelligence (AI) are now widely accessible. This article examines distinct aspects and comparative advantages of AI and human translation through an analysis of their approaches, abilities, drawbacks and chances for collaboration. Thus, the study compared AI and human translation, looking at their respective advantages and disadvantages as well as the circumstances in which they would work best. It did this by employing a contrastive methodology.